2010
DOI: 10.1093/toxsci/kfq098
|View full text |Cite
|
Sign up to set email alerts
|

The Glutaredoxin/Glutathione System Modulates NF-κB Activity by Glutathionylation of p65 in Cinnamaldehyde-Treated Endothelial Cells

Abstract: Reversible protein glutathionylation is an important posttranslational modification that provides protection against oxidation. In endothelial cells (ECs), cinnamaldehyde is an electrophilic compound that can increase the intracellular glutathione (GSH) levels or reactive oxygen species (ROS) production depending on the treatment duration. ECs treated with GSH and H(2)O(2) show increased sulfhydryl modifications of the p65 subunit of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kappaB), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 42 publications
6
36
0
Order By: Relevance
“…treated endothelial cells, leading to an inhibition of NF-kB p65 nuclear translocation [12]. In vitro, NF-kB p50-SSG inhibited the capacity of NF-kB to bind DNA [13].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…treated endothelial cells, leading to an inhibition of NF-kB p65 nuclear translocation [12]. In vitro, NF-kB p50-SSG inhibited the capacity of NF-kB to bind DNA [13].…”
Section: Discussionmentioning
confidence: 94%
“…One such reversible modification is protein glutathionylation (protein-SSG), whereby a cysteine-thiol of a protein (protein-SH), forms a disulfide bond with the cysteine-thiol of glutathione (GSH). Protein-SSG is inducible by reduction of the AFFILIATIONS *Respiratory Research Group, Faculty of Pharmacy, intracellular GSH level [11] and has been shown to result in an inhibition of NF-kB nuclear entry and binding to DNA [12,13]. Dimethylfumarate (DMF) reduces cellular glutathione in many different cell types [14][15][16], and has also been shown to inhibit the nuclear entry of NF-kB and subsequent binding to DNA in ASMCs [7].…”
mentioning
confidence: 99%
“…Glutathionylation has been shown to play a regulatory role in the activity of various proteins, in a manner similar to the regulatory changes induced by protein phosphorylation (Beer et al, 2004;Chen et al, 2007;Mueller et al, 2008;Townsend et al, 2009;Bundgaard et al, 2010;Hawkins et al, 2010;Liao et al, 2010;Yang et al, 2011). Therefore, alteration of the glutathionylation status of hepatocellular proteins after hepatotoxicant insult could lead to altered function of key proteins and subsequent cellular injury.…”
Section: Changes In Protein Glutathionylation After Apap Exposure 365mentioning
confidence: 99%
“…Glutathionylation depends on Glutaredoxin (GRX) and thioredoxin levels (deglutathionylation enzymes) and on the increase in the cellular GSH/GSSG ratio, which also exert a reversible action on protein S-glutathionylation. Interestingly Akt [96], NFκB [97], and other protein like eNOS or MEKK1 [98,99] are also subject to glutathionylation. This mechanism of regulation may be a masterpiece in the understanding of DHEA effect as a peroxysome proliferator.…”
Section: Discussionmentioning
confidence: 99%